2021
DOI: 10.1101/2021.05.29.21258010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid and sustained decline in CXCL-10 (IP-10) annotates clinical outcomes following TNF-α antagonist therapy in hospitalized patients with severe and critical COVID-19 respiratory failure

Abstract: Background: A feed-forward pathological signaling loop generated by TNFα and IFN-γ in inflamed lung tissue, driving CXCL-10 (IP-10) and CXCL-9 chemokine-mediated activated T-cell and monocyte/macrophage tissue recruitment, may define, sustain and amplify the inflammatory biology of lethal COVID-19 respiratory failure. Methods: To assess TNFα-antagonist therapy, 18 hospitalized adults with hypoxic respiratory failure and COVID-19 pneumonia received single-dose infliximab-abda therapy 5mg/kg intravenously betwee… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…It is known that BAFF can promote CD4 + T cell IFN production and CD8 + T cell cytotoxicity in chronic obstructive pulmonary disease (COPD) (42), supporting the concept that it may be part of a positive feedback loop that sustains non-specific cytotoxic lymphocyte activation in COVID-19. It is also likely that elevated levels of IL-1, IL-6 and TNF may contribute to dysregulation of CD8 T cells, NK cells and macrophages as part of the so-called 'cytokine storm' (26,43).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that BAFF can promote CD4 + T cell IFN production and CD8 + T cell cytotoxicity in chronic obstructive pulmonary disease (COPD) (42), supporting the concept that it may be part of a positive feedback loop that sustains non-specific cytotoxic lymphocyte activation in COVID-19. It is also likely that elevated levels of IL-1, IL-6 and TNF may contribute to dysregulation of CD8 T cells, NK cells and macrophages as part of the so-called 'cytokine storm' (26,43).…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study (NCT04425538) reported results that infliximab treatment improved oxygenation and eliminated pathological inflammatory signals. 361 Most of these are still being evaluated for their clinical effectiveness. Adalimumab is registered in two clinical trials (NCT04705844 and ChiCTR2000030089), and infliximab is also in four clinical trials (NCT04922827, NCT04734678, NCT05220280, and NCT04593940).…”
Section: Tnf-α Inhibitorsmentioning
confidence: 99%
“…The current use of inhibitors against TNF‐α for the treatment of COVID‐19 mainly includes monoclonal antibodies, such as adalimumab, golimumab, infliximab, certulizumab, and the TNF‐α receptor fusion protein etanercept. A clinical study (NCT04425538) reported results that infliximab treatment improved oxygenation and eliminated pathological inflammatory signals 361 . Most of these are still being evaluated for their clinical effectiveness.…”
Section: Intervention Therapymentioning
confidence: 99%
“…As far as TNFα inhibitors exclusively meant for an anti-COVID-19 treatment are concerned, a clinical trial evaluating adalimumab has been reported in China (ChiCTR2000030089). Furthermore, a completed phase II clinical trial showed that infliximab may extinguish the pathological inflammatory signaling providing clinical recovery in severe COVID-19 [ 181 ]. Indeed, the results of further clinical trials are necessary, to better elucidate the role and the timing of TNF inhibitors in COVID-19 treatment.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%